Pengaruh Persepsi Mahasiswa, Motivasi Karir Dan Lingkungan Kerja Auditor Terhadap Minat Mahasiswa Akuntansi Menjadi Seorang Auditor - Ni Putu Ayu Fitry Swandewi; Sang Ayu Putu Arie Indraswarawati; I Wayan Budi Satriya (UNHI Press, 2022)
Auditor is a profession that has an important role in the company. It is not surprising that the need for auditors in Indonesia is always increasing, in line with this, it is expected that students majoring in accounting will later become auditors after completing their education. Seeing the existing phenomena, the researcher is interested in conducting research with theaim of analyzing the relationship between student perceptions, career motivation and auditor work environment on the interest of accounting students to become an auditor (a case study on students majoring in accounting at UNHI). In this case, the active students of S1 Accounting Study Program, Faculty of Economics, Business and Tourism, Hindu Indonesia University class of 2019 semester 6 are the overall research population with a total sample of 131 people. This research will use multiple linear regression analysis techniques to get answers to the formulation of the problem. The results showed that student perceptions, career motivation, auditor's work environment can affect student interest in deciding in the future to become an auditor or not.